Clinical implications of next‐generation sequencing‐based panel tests for malignant ovarian tumors. (19th August 2020) - Saotome, Keiko; Chiyoda, Tatsuyuki; Aimono, Eriko; Nakamura, Kohei; Tanishima, Shigeki; Nohara, Sachio; Okada, Chihiro; Hayashi, Hideyuki; Kuroda, Yuka; Nomura, Hiroyuki; Susumu, Nobuyuki; Iwata, Takashi; et al.
Abstract: Precision medicine based on cancer genomics is being applied in clinical practice. However, patients do not always derive benefits from genomic testing. Here, we performed targeted amplicon exome sequencing‐based panel tests, including 160 cancer‐related genes (PleSSision‐160), on 88 malignant ovarian tumors (high‐grade serous carcinoma, 27; endometrioid carcinoma, 15; clear cell carcinoma, 30; mucinous carcinoma, 6; undifferentiated carcinoma, 4; and others, 6 (immature teratoma, 1; carcinosarcoma, 3; squamous cell carcinoma, 1; and mixed, 1)), to assess treatment strategies and useful biomarkers for malignant ovarian tumors. Overall, actionable gene variants were found in 90.9%, and druggable gene variants were found in 40.9% of the cases. Actionable BRCA1 and BRCA2 variants were found in 4.5% of each of the cases. ERBB2 amplification was found in 33.3% of mucinous carcinoma cases. Druggable hypermutation/ultramutation (tumor mutation burden ≥ 10 SNVs/Mbp) was found in 7.4% of high‐grade serous carcinoma, 46.7% of endometrioid carcinoma, 10% of clear cell carcinoma, 0% of mucinous carcinoma, 25% of undifferentiated carcinoma, and 33.3% of the other cancer cases. Copy number alterations were significantly higher in high‐grade serous carcinoma ( P < .005) than in other histologic subtypes; some clear cell carcinoma showed high copy number alterations that were correlated with advanced stage ( P < .05) and worse survival ( P < .01). A high count of copy number alteration was associated with worse survival in all malignant ovarian tumors ( P < .05). Our study shows that targeted agents can be detected in approximately 40% of malignant ovarian tumors via multigene panel testing, and copy number alteration count can be a useful marker to help assess risks in malignant ovarian tumor patients. Abstract : Next‐generation sequencing‐based panel tests on 88 malignant ovarian tumors revealed that targeted agents can be detected in approximately 40% of malignant ovarian tumors. Copy number alteration count was found to be a useful marker to help assess risks in malignant ovarian tumor patients.